(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to define the theoretical framework for corporate governance and its mechanisms and shed light on corporate governance in Iraq as well as the theoretical framework for the quality of financial reports and their relationship and the role of corporate governance in activating them. A commercial bank as a sample for the research, and a survey list was prepared to show the extent to which the research sample banks are committed to applying internal governance mechanisms. imposed on them by the local environment, which leads to improving the quality of financial reports for these banks.